Porcine epidemic diarrhea virus (CV 777) and feline infectious peritonitis virus (FIPV) are antigenically related - Yaling, Zhou (Arch Virol, 1988)
Using gut sections from pigs infected with porcine epidemic diarrhea virus (strain CV 777) and ascitic fluid from cats which had succumbed to feline infectious peritonitis (FIP), a weak cross reaction was found by immunofluorescence. Its specificity was confirmed when detergent-treated purified CV 777 showed a prominent reaction with FIPV antibodies in ELISA; no reaction was obtained with intact virions, which indicated common determinants on an internal component of the particle. Antigenic cross-reactions at the nucleocapsid level were found in Western blot ELISA performed both ways (CV 777/FIPV antibodies; FIPV/CV 777 antibodies). In immunoprecipitation using [(35)S]methionine labelled FIPV, anti-CV 777 sera recognized exclusively the nucleocapsid protein. The significance of these findings for the classification of coronaviruses is discussed.